Urgensi Pembentukan Unit Usaha Masjid sebagai Pemberdayaan Ekonomi Ummat - M Endang Asmara; Zenni Riana; Ahmad Rizki Harahap; Amirulsyah Amirulsyah (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2022)
At the time of the Prophet Muhammad, the mosque was used as a center for Muslim activities, such as the center of worship, government, politics and the economy. Economic institutions located in the mosque environment will be the safest investment places. It can be seen the physical construction of the mosque which is increasingly magnificent and beautiful, and the crowds of the community if inviting the popular Da'I. This can be more useful in a more productive way, namely by collaborating with MSMEs in the mosque environment to open up the widest possible employment opportunities. The COVID-19 pandemic has had an impact on the MSME sector, which has experienced a decline in marketing due to the difficult economy. In addition, it also causes social impacts such as in4creasing unemployment and children dropping out of school. So it is necessary that the Mosque Economic Institute can be a support in the economy. The research method uses descriptive qualitative methods through interviews (interviews), field surveys, and documentation. The place of research is a mosque in Medan Municipality. The results of the study are recommendations to the Medan City Government and build a Mosque-Based Economic Institution Model in accordance with Mission 1 Medan Berkah, Program 3: Aid for Houses of Worship and Activation of Economic Institutions/Cooperatives for Houses of Worship Target Number 3 Establishment of an economic economic institution for the people assisted by the Medan City Government.